Multi-Capital Approach for Sustainable Growth: Experience from the Oil & Gas Companies - A. N. Steblyanskaya; Ai. Mingye; O. V. Efimova; G. B. Kleiner; M. А. Rybachuk (Финансы: теория и практика, 2022)
Nowadays, companies traditionally use economic capital and follow the interests of profit-making by shareholders or financial structures. However, recently there has been a tendency to analyze non-financial factors affecting equity. Multicapitalism is a doctrine that studies the impact of social, environmental, and economic indicators on equity. The subject of the study is the Chinese oil and gas companies’ sustainable growth. The paper’s purpose is to consider the interdependence of non-financial indicators with the Higgins Sustainable Growth Rate (SGR) and the Ivashkovskaya Sustainable Growth Index (SGI). The primary task is to solve the problems faced by China oil and gas companies regarding the introduction of non-financial reporting. The methodological basis of the study is a regression analysis of the influence of non-financial factors on sustainable growth indices. The authors analyze the impact of non-financial factors EROI, PRP, ES, ROEenv, ROL, ROEsr on the China oil and gas companies’ SGR and SGI. It is shown that non-financial indicators show a stronger correlation with SGR than SGI. The study’s main conclusion is that there is a significant positive correlation between individual non-financial indicators and sustainable growth indices. The practical application of the obtained research results is seen in the development of non-financial reporting of oil and gas companies in China by including indicators EROI, PRP, ES, ROEenv, ROL, ROEsr to assess the work of sustainable growth of the enterprise.